(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The headway of the Digital Technology helps compelling investment of women in the dynamic and execution measure identified with science and innovation including arranging and setting needs for innovative work and the decision, securing, selection, advancement and utilization of science and innovation for the turn of events. A business visionary is an individual who has a venturesome quality with an eye on promising circumstances and an uncanny vision, an individual who will face challenges due to the bold ability inside, same holds useful for women too. The current proposal attempts to examine the idea of women business person and difficulties looked by them in India. This paper is for the most part dependent on optional information and perceptions for the distinguishing proof of these issues the writers have explored distinctive exploration articles and reports. Discoveries of this investigation uncover that shortfall of harmony among family and profession, socio-social obstructions, male ruled society, illiteracy or low degree of schooling, shortage of monetary help, absence of specialized expertise, showcasing and pioneering abilities, absence of self-assurance and versatility imperatives are serious issues of women business improvement. A few ideas have been furnished to manage this issue.